The ethical imperative leading with conscience to shape the future of business - Cooper, Andrew C. M. (Ascent Audio, 2024)
In an era marked by increasing profiteering and inequality, The Ethical Imperative offers a compelling alternative vision-one where companies champion the collective prosperity of employees, shareholders, and communities. Andrew C. M. Cooper, a distinguished executive, leverages over twenty academic studies and fifty years of research to challenge the status quo. He exposes the critical threat of public disengagement from businesses and institutions, urging a departure from outdated, profit-only models that harm corporations, consumers, and communities alike.
Online resource; title from title details screen (O'Reilly, viewed September 24, 2024)
Keywords: Business ethics; Social responsibility of business; Leadership; Morale des affaires; Entreprises; Responsabilité sociale; Audiobooks; Livres audio